Analisis Faktor-Faktor yang Mempengaruhi Kepuasan Pengguna Terhadap Layanan Mandiri Mobile Banking di Kediri - Lusdianingrum, Sitista Silvi; Rahayuningtyas, Tri Esti (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the influence of cost, security, relative advantage, responsiveness, and ease of use on user satisfaction with Livin by Mandiri mobile banking services in Kediri. This study uses a quantitative method with 172 respondents selected through purposive sampling to collect data from active users of Livin by Mandiri services, which are then analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS. The results of this study indicate that the five independent variables have a positive and significant effect on user satisfaction. Convenience is the most dominant factor (t=3.750; p=0.000), followed by security (t=3.495; p=0.000), relative advantage (t=3.372; p=0.001), cost (t=2.869; p=0.004), and responsiveness (t=2.483; p=0.013). The research model shows an Adjusted R-Square value of 0.671, which means that 67.1% of the user satisfaction variables can be explained by these five variables. The results of this study indicate that user satisfaction is formed through technical ease of use, high security, and system reliability. For banking companies, these results show the importance of maintaining cost efficiency and service responsiveness to build long-term user loyalty. This study supports the application of the Technology Acceptance Model (TAM) and Diffusion of Innovation (DOI) in the development of digital banking services in Kediri.